First impressions count: Almost double! : A study of the interaction of interviewer appearance and information effects in stated preference studies - Ian J. Bateman; James Mawby (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
A simple but novel experiment is described examining the impact of interviewer appearance upon stated willingness to pay (WTP) for an environmental good. This test consists of an interviewer wearing either formal or more casual clothing. This analysis is interacted with a cross cutting treatment examining the more familiar impact of adding information on certain of the less familiar attributes of the good in question. Face to face interviews are employed to collect a sample of respondents who are randomly allocated to one of the four treatment permutations described by our interviewer appearance and information change study design. Our analysis suggests that both altering the appearance of an interviewer and changing the degree of information provided can have significant impacts upon stated WTP. Furthermore this effect is heightened when both effects are running in parallel. We argue that such findings are to be expected given the highly interactive nature of face-to-face interviewing but note that this serves to provide a cautionary note regarding the complex array of influences at work when members of the public are asked to express preferences regarding goods for which they have not previous provided monetary values.
Keywords: 330; Appearance; Information effect; Contingent valuation; Interviewer effect; Stated preference; Willingness to pay (WTP); Willingness to pay; Befragung; Offenbarte Präferenzen